THE STRUCTURE AND INFLUENCE OF THE MEDIA SPHERE AND THE CULTURE OF INFORMATION DISSEMINATION (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This article examines the structure of the modern media sphere, its influence on public perception, and the culture of information dissemination in the digital era. As media platforms expand and diversify, their role in shaping social attitudes, political behavior, and cultural norms becomes increasingly significant. The study highlights the components of the media ecosystem, the mechanisms through which media affects audiences, and the ethical principles required for responsible information sharing. Particular attention is given to challenges such as misinformation, digital manipulation, and the decline of traditional gatekeeping. The article concludes with recommendations for promoting media literacy, transparency, and a healthier information environment.